The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1063/1.4754271
|View full text |Cite
|
Sign up to set email alerts
|

Small particles, big impacts: A review of the diverse applications of nanofluids

Abstract: Nanofluids—a simple product of the emerging world of nanotechnology—are suspensions of nanoparticles (nominally 1–100 nm in size) in conventional base fluids such as water, oils, or glycols. Nanofluids have seen enormous growth in popularity since they were proposed by Choi in 1995. In the year 2011 alone, there were nearly 700 research articles where the term nanofluid was used in the title, showing rapid growth from 2006 (175) and 2001 (10). The first decade of nanofluid research was primarily focused on mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
291
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(313 citation statements)
references
References 295 publications
1
291
0
4
Order By: Relevance
“…1,2 This has suggested a remarkably simple way to improve the thermal conductivity of thermal fluids (which is generally low), through the dispersion of small amounts of a dispersed solid. The energy savings that could be achieved by colloidal thermal fluids (nanofluids) has prompted several investigations into their thermal properties, and particularly into the enhancement of the thermal conductivity of the base fluid in the presence of colloidal particles.…”
mentioning
confidence: 99%
“…1,2 This has suggested a remarkably simple way to improve the thermal conductivity of thermal fluids (which is generally low), through the dispersion of small amounts of a dispersed solid. The energy savings that could be achieved by colloidal thermal fluids (nanofluids) has prompted several investigations into their thermal properties, and particularly into the enhancement of the thermal conductivity of the base fluid in the presence of colloidal particles.…”
mentioning
confidence: 99%
“…The characteristic feature of nanofluid is the thermal conductivity enhancement, a phenomena observed by Masuda et al [8]. Philip and Shima [9], Keblinski et al [10], Wong and Leon [11], Yu and Xie [12], Taylor et al [13] reported the developments in the study of heat transfer, using nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Nano particles research has intense scientific interest due to many potential application in versatile fields such as biomedical, optics and electronic fields [19]. One of the interesting technologies regarding the metal nano particles is thin coatings and layers of materials [20].…”
Section: Metal Nano Layer Preparationmentioning
confidence: 99%